Synthesis of Calcium Phosphate from Snail Shell Waste Using the Hydrothermal Method - Ananda Arif Rochman; Nazila Aulya Rahman; Sani Sani; Caecilia Pujiastuti; Ika Nawang Puspitawati (G-Tech: Jurnal Teknologi Terapan, 2026)
The utilization of biowaste as an alternative raw material has attracted increasing attention in biomaterial research. Snail shell waste, which is abundant and underutilized, contains a high calcium carbonate content and offers a unique, low-cost, and sustainable precursor for calcium phosphate synthesis, particularly for bone substitute applications. This study aimed to synthesize calcium phosphate from snail shell waste using the hydrothermal method and to evaluate the effects of pH and hydrothermal time on phase formation, purity, and particle size. The shells were calcined at 800 °C for 4 hours to produce calcium oxide (CaO), then reacted with phosphoric acid at pH 8–12 under hydrothermal conditions for 25–125 minutes. The precipitates were dried and sintered at 1000 °C for 5 hours. X-ray fluorescence analysis showed a CaO content of 99.20%. X-ray diffraction revealed calcium hydrogen phosphate, hydroxyapatite, and calcium carbonate phosphate hydroxide phases. The highest hydroxyapatite content (54%) was obtained at pH 8 and 25 minutes. Higher pH and longer processing time reduced purity. Scanning electron microscopy showed granular morphology, with particle sizes decreasing from 63 nm to 28 nm as pH increased. Although promising, the hydroxyapatite content does not yet meet RSNI3 ISO 13175-3:2012 requirements.